Bases teóricas de gestao da informaçao: das origens aos desafios na sociedade contemporânea - Belluzzo, Regina Celia Baptista (2017)
It presents a scenario of information management, with reflections about its theoretical bases, origins and the main challenges that this area must face in the contemporary society, whose characteristics bring with it demands and information needs that require new conducts of management and protagonism of the organizations, with a special emphasis on libraries and the professionals that work in it, in relation to the theme that guides communities towards the feasibility of sustainability. Considerations are offered on the importance of information management as a preponderant factor to help the process of dissemination of information, as a strategy to raise awareness of the communities involved, considering that those who have access to properly managed information considered relevant, at the right time and intelligently utilized, can be labeled as information literate and able to eradicate poverty and inequality, improve agriculture, provide quality education and promote health, culture, research and innovation - Important themes for this area of management in the world contemporary